39x - 45 = 15x - 24
divide by 3: 3(6x2 + 13x - 5) Look for factors of 6 which can be multiplied by factors of -5 and added to give 13. Factors of 6: 1 & 6; 2 & 3; Factors of -5: -1 & 5; -5 & 1 the last and first ones give 3 x -5 = -15 and 2 x 1 = 2, total 13 so: 3(3x - 1)(2x + 5) = 3(6x2 - 2x + 15x - 5) = 18x2 + 39x - 15
(2x - 7)(7x + 5)
14x2 - 39x - 35 = (7x + 5)(2x - 7)
It is a quadratic expression and when factored it is: (7x+5)(2x-7)
(7x + 5)(2x - 7)(2x-7)(7x+5)
39x-6
3x2-39x-90 = (3x+6)(x-15) when factored
41x
2x - 3= 9 x=
2 - 39x - 50 = 4 + x -39x - 48 = 4 + x Add 39 x to both sides: -48 = 4 + 40x Subtract 4 from both sides: -52 = 40x Divide both sides by 40: x = -1.3
For x-2x= 3x-43x+1 x-2x= -x and 3x-43x+1 = -40x+1 so -x= -40x+1 subtract -x from both sides 0= -39x +1 -1 = -39x so 1=39x so x=1/39
(7x - 5)(5x - 2)
-38y - 39x (Is that what you were asking for?)